PENGARUH VARIABEL MAKROEKONOMI DAN INDEKS SAHAM INTERNASIONAL TERHADAP INDEKS SAHAM JAKARTA ISLAMIC INDEX (JII) - Devi Rahmiyanti; Bayu Arie Fianto (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study investigate the effect of macroeconomic variables and international stock index on the stock index Jakarta Islamic Index (JII) using monthly data over period January 2013 to December, 2018. Macroeconomic variables used in this study are inflation, exchange rate, international crude oil price, World Gold Price and for the international stock index using Dow Jones Islamic Market. The study employs the eror correction model (ECM). The empirical result reveal that there is co-integration between the four macroeconomic variables, one international stock index and stock index in Jakarta Islamic Index indicating long run equilibirium relationship. Furhther, the result reveal that with significancy 0,5% only exchange rate, international crude oil price, world gold price had significant effect on Jakarta Islamic Index while inflation and Dow jones Islamic Market did not have a significant effect on Jakarta Islamic Index.Keywords: The stock Index, the Jakarta Islamic Index, the macroeconomic variables